RIVER CAPACITY ANALYSIS AFFECTED BY THE TIDE - Akhmad Taruna Rasyidi; Maya Amalia; M. Azhari Noor (CERUCUK, 2017)
Anjir Mulawarman is one of the canals in Banjarmasin. Anjir Mulawarman has a geometric shape that is straight with the street on both sides and riverbanks form gravity retaining wall. However, when the tide is still some places such as houses and streets that were around the riverbanks run into puddles. This final project discusses about the capacity of each cross-section of the river are experiencing water runoff when the high tide and also plans riverbank that safe against the tide.The method used is the field research in the form of geometrical data every 50 meters conducted along the river and tidal data in the upstream and downstream for 15 days through Admiralty. The field data were analyzed through a support program HEC-RAS 5.0 will get a cross-section tide experiencing water runoff and will get a safe levee elevation plans.The Results of the research showed that Anjir Mulawarman is 1.88 km, the river channel width is 16-39 meters, and the channel depth is 2.28 to 3.66 meters. The number of stations that were flooded due to tidal  as many as 14 of the total 39 stations, with the water level varied from 6 cm to 20 cm in the riverbank area including houses and streets. This cross-sectional capacity of 14 stations are not able to accommodate the tide, so it will planning levee or raising the banks to at least 7.5 meters above sea level elevation. Keyword : Anjir Mulawarman, Channel Cross Section, Tide, HEC-RAS 5.0